2009
DOI: 10.1007/s11224-009-9496-y
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies of five-membered ring ketene acetals

Abstract: Cyclic ketene acetals are a class of organic molecules characterized by a nucleophilic exo-methylene carbon attached to a carbon with two adjacent O, N, or S atoms. We have carried out a systematic computational study of a series of five-membered cyclic acetals like 2-methylene-1,3-dioxolane and its OS, SS, NO, NS, and NN analogs as well as all the protonated species. The calculations were performed at the MP2 level using a triple zeta plus polarization basis set. The nucleophilicity was discussed in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…All structures were initially optimized at the B3LYP [34, 35]/6-311?G(d) [36] level of theory. Vibrational analysis of these structures revealed that some of the optimized structures had one imaginary frequency.…”
Section: Computational Detailsmentioning
confidence: 99%